2016
DOI: 10.5430/jha.v5n5p91
|View full text |Cite
|
Sign up to set email alerts
|

Lean in healthcare: Engagement in development, job satisfaction or exhaustion?

Abstract: Conclusions about implementing the management concept lean in healthcare are contradictory and longitudinal studies are scarce. In particular, little is known of how working conditions contribute to the sustainability of lean in healthcare. The aim of this article is to identify to what extent lean tools (visual follow-up boards, standardised work, 5S [housekeeping], and value stream mapping [VSM]) promote working conditions for employees and managers in healthcare organisations (outcomes: engagement in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 72 publications
3
24
1
2
Order By: Relevance
“…Staff engagement includes, according to Macey and Schneider [42], commitment, involvement, energy, enthusiasm, empowerment, taking initiative, willingness to accept changes and assuming responsibility. In a longitudinal study in primary care, engagement increased after Lean adoption [11], a finding also described in other studies focused on the healthcare sector [24, 31, 43]. Further, there might be a relationship between working conditions and thriving, as described by Leiter and Bakker [23].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Staff engagement includes, according to Macey and Schneider [42], commitment, involvement, energy, enthusiasm, empowerment, taking initiative, willingness to accept changes and assuming responsibility. In a longitudinal study in primary care, engagement increased after Lean adoption [11], a finding also described in other studies focused on the healthcare sector [24, 31, 43]. Further, there might be a relationship between working conditions and thriving, as described by Leiter and Bakker [23].…”
Section: Introductionsupporting
confidence: 52%
“…Leiter and Bakker suggested that having job resources could also enhance thriving at work [23]. Empirical studies from the healthcare sector have shown that having high job demands contributed to increased exhaustion [24, 25]; however, in a study of knowledge workers (e.g., professors, scientists, engineers, teachers, managers, secretaries and physicians), high job demands improved job performance [26]. Apart from the dual processes, in the JD-R theory, Bakker and Demerouti [19] also suggested that an interaction effect exists between job demands and resources, claiming that “job resources can buffer the impact of job demands on strain” ([19], p., 274) and that “job resources particularly influence motivation when job demands are high” ([19], p., 275).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research stated that the use of VM tools in combination with low job resources (i.e., job security) would have negative effect on healthcare staff's job satisfaction (Lindskog et al., ). Nurses’ working conditions being strained by the complex core tasks of hospital work (Carayon et al., ; Holden, ; Patel et al., ) and demands of participating in care process redesign could surely affect nurses’ job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study concerning the use of tools inspired by lean production, including VM tools, during healthcare improvement work may promote staff's working conditions (Dellve et al., ). While another study set in the same setting showed that the combination of use of visual follow‐up boards not supported by job resources, such as job security, had a negative effect on staff's job satisfaction and further that the use of VM tools was deteriorating over time (Lindskog, Hemphälä, Eklund, & Eriksson, ).…”
Section: Introductionmentioning
confidence: 99%
“…As employee participation is very important in lean management applications (31,32), employees are required to know the lean management terms and the lean management tools. For this purpose, training programs covering lean management concepts and definitions, techniques used in lean management practices and examples of lean management in health institutions were organized.…”
Section: Phase 3: Training Of Employeesmentioning
confidence: 99%